Determinants of Sovereign Investment Protectionism: the Case of Bulgaria’s Nuclear Energy Sector - Iankova, Elena A.; Tzenev, Atanas G. (Organizations and Markets in Emerging Economies, 2015)
Foreign direct investment (FDI) by entities controlled by foreign governments (especially state-owned enterprises) is a new global phenomenon that is most often linked to the rise of emerging markets such as China and Russia. Host governments have struggled to properly react to this type of investment activity especially in key strategic sectors and critical infrastructure that ultimately raise questions of national security. Academic research on sovereign investment as a factor contributing to the new global protectionist trend is very limited, and predominantly focused on sovereign investors from China. This study explores the specifics of Russian sovereign investment in the former Soviet Bloc countries, now members of the European Union, especially in strategic sectors such as energy. We use the case of Bulgaria’s nuclear energy sector and the involvement of Russia’s state-owned company Rosatom in the halted Belene nuclear power plant project to analyze the dynamics of policy and politics, political-economic ideologies and historical legacies in the formation of national stances towards Russia as a sovereign investor. Our research contributes to the emerging literature on FDI protectionism and sovereign investment by emphasizing the significance of political-ideological divides and the heritage of the past as determinants of sovereign investment protectionism.
Keywords: foreign direct investment policy; state-controlled entities; national security; nuclear energy; post-communist countries